1999
DOI: 10.1097/00000539-199905000-00038
|View full text |Cite|
|
Sign up to set email alerts
|

Which Countries Publish in Important Anesthesia and Critical Care Journals?

Abstract: In a MEDLINE-based analysis, we examined the number of publications in important anesthesia, pain, critical care, and emergency medicine journals (n = 30) for the years 1996 and 1997 and analyzed these with regard to national origin. The United States was by far the most active nation in this medical area (4283 articles [40.2%]), followed by the United Kingdom (13.3%). With regard to publications per million inhabitants, small highly industrialized nations contributed overproportionally to publications in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 10 publications
1
21
1
3
Order By: Relevance
“…The United States also ranked first in editorials, review articles, case reports and in all articles combined; it ranked second in correspondence and other unspecified articles ( Fig. 1 [2].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The United States also ranked first in editorials, review articles, case reports and in all articles combined; it ranked second in correspondence and other unspecified articles ( Fig. 1 [2].…”
Section: Resultsmentioning
confidence: 98%
“…Countries were ranked in order of productivity. To facilitate comparisons with previous data [2], an analysis was performed firstly for all journals and then for English language journals. As a secondary outcome the number of original articles for each country and each journal was multiplied by the 2007 impact factor for that journal in an attempt to provide an adjustment for the quality of the publication.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of countries or groups of countries to journals or conferences has been explored since 1980s (Schubert, Glänzel, & Braun, 1989;Braun, Glänzel, & Schubert, 1985;Schubert, Zsindely, & Braun, 1983). Some studies have investigated country distributions of publications in a few high-impact journals; most have been carried out on specific fields of science and reported that most papers in high-quality journals come from researchers in the U.S. and U.K., with few from developing countries (Elliott, Greenaway, & Sapsford, 1998;Black & Davies, 1999;Boldt, Maleck & Koetter, 1999;Carnegie & Potter, 2000;Patel & Sumathipala, 2001;Jones & Roberts, 2005;Mahawar, Malviya, & Kumar, 2006;Cheung, 2009). Indeed, the chance of being accepted in an American journal is lower for submissions from countries other than the U.S. (Elster and Chen, 1994) and also the acceptance rate of papers from highincome countries is about five times greater than that of papers from low-and middle-income countries (Singh, 2006).…”
Section: Journal Publishing Behaviourmentioning
confidence: 99%
“…It seems the quality of references in a paper positively influences its visibility and impact (Boyack & Klavans, 2005;Lancho-Barrantes, Guerrero-Bote, & MoyaAnegon, 2010;Bornmann, Schier, Marx, & Daniel, 2011) and hence it may be that lack of access to high quality journals prevents developing countries" researchers from producing high quality successful publications. Developed countries publish the majority of their papers in leading journals, with few papers originating from less developed countries (Mahawar, Malviya & Kumar, 2006;Boldt, Maleck & Koetter, 1999;Elster & Chen, 1994). Some studies have tried to identify the reasons behind this.…”
Section: Introductionmentioning
confidence: 99%